Pengaruh Kualitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Komitmen Organisasi terhadap Ketepatwaktuan Pelaporan Keuangan Pemerintah Nagari - Annisa Maharani; Henri Agustin (Universitas Negeri Padang, 2021)
This study aims to determine the effect of the quality of human resources, the use of information technology and organizational commitment to the timeliness of financial reporting by the village government (empirical study on Village Government of Tanah Datar Regency). This study uses subject data. The sampling technique used the total sampling method with a sample size of 75 villages. The data analysis used multiple linear regression analysis. The results showed that the quality of human resources and organizational commitment had a positive and significant effect on the timeliness of the Village government financial reporting. Information technology has no effect on the timeliness of the Village government financial reporting.